The Relaying Network in Free-Space Optical Communications using Optical Amplifiers in Cascaded Configuration - Darusalam, Ucuk; Raj, Arockia Bazil; Zulkifli, Fitri Yuli; Priambodo, Purnomo Sidi; Rahardjo, Eko Tjipto (Makara Journal of Technology, 2023)
Optical relaying is the best technique to implement free-space optical (FSO) communications as a terrestrial platform. However, atmospheric turbulence (AT) limits the optical-propagation path length. In this study, the implementation of some optical amplifiers (OAs) in cascaded configuration, namely, erbium-doped fiber amplifiers, semiconductor OAs, and Raman amplifiers (RAs), are investigated through simulation. This study aims to search for the maximum link distance of an optical propagation and enhance the FSO performance caused by each configuration of OAs. The optical relaying network consists of three nodes, with each node designed with a space of several kilometers under the influence of AT. At the end of the destination, before the receiver, an optical band-pass filter is applied to perform noise filtering. Among the OAs in the cascaded configuration, the RA can expand the link distance of the optical-propagation path length to a range of 14.7–15.9 Km under the influence of a strong AT. The signal-to-noise ratio and bit error rate of the system are in the ranges of 24.1– 19.08 dB and 7.9 × 10−15–7.4 × 10−6, respectively.